Analisis Kemampuan Creative Thinking dalam Memecahkan Masalah Open-Ended ditinjau dari Gaya Belajar Siswa - Tika Tri Suryani; Ulum Fatmahanik (Institut Agama Islam Negeri Ponorogo, 2025)
This research aims to (1) determine the ability of creative thinking in solving open ended problems in terms of students' learning styles, (2) determine the level of creative thinking abilities in solving open ended problems in terms of students' learning styles, (3) determine the factors that influence creative abilities thinking in solving open ended problems in terms of student learning styles. This research method uses qualitative with descriptive research type. The research location is MI Ma'arif Sabilul Mttaqin. The subjects taken in this research were 6 students with 2 students representing each learning style. The instruments used were a learning style questionnaire sheet, a creative thinking ability test sheet based on open-ended questions, and an interview sheet. The data analysis technique used is qualitative data analysis, with the steps of data condensation, data presentation, and drawing conclusions. The results of the research show that, (1) The creative thinking abilities of students with a visual learning style are able to meet the indicators of fluency and flexibility, but are not able to meet the indicators of novelty. Students with an audiotorial learning style are able to meet the indicators of fluency and flexibility, but are not able to meet the indicators of novelty. Students with a kinesthetic learning style are able to meet the fluency indicators, but are unable to meet the flexibility and novelty indicators. (2) The creative thinking abilities of students with a visual learning style are at level 3 (creative), students with an audiotorial learning style are at level 3 (creative), and students with a kinesthetic learning style are at level 1 (less creative). (3) Factors that influence students' creative thinking abilities generally come from external factors, namely class conditions, lack of familiarity with working on open ended questions, and only being able to work on questions taught by the teacher.